Neurosensory analysis of tooth sensitivity during at-home dental bleaching: a randomized clinical trial - André Luiz Fraga Briso; Vanessa Rahal; Fernanda Almeida de Azevedo; Marjorie de Oliveira Gallinari; Rafael Simões Gonçalves; Paulo Henrique dos Santos; Luciano Tavares Angelo Cintra (University of São Paulo, 2018)
Abstract Objective The objective of this study was to evaluate dental sensitivity using visual analogue scale, a Computerized Visual Analogue Scale (CoVAS) and a neurosensory analyzer (TSA II) during at-home bleaching with 10% carbamide peroxide, with and without potassium oxalate. Materials and Methods Power Bleaching 10% containing potassium oxalate was used on one maxillary hemi-arch of the 25 volunteers, and Opalescence 10% was used on the opposite hemi-arch. Bleaching agents were used daily for 3 weeks. Analysis was performed before treatment, 24 hours later, 7, 14, and 21 days after the start of the treatment, and 7 days after its conclusion. The spontaneous tooth sensitivity was evaluated using the visual analogue scale and the sensitivity caused by a continuous 0°C stimulus was analyzed using CoVAS. The cold sensation threshold was also analyzed using the TSA II. The temperatures obtained were statistically analyzed using ANOVA and Tukey's test (α=5%). Results The data obtained with the other methods were also analyzed. 24 hours, 7 and 14 days before the beginning of the treatment, over 20% of the teeth presented spontaneous sensitivity, the normal condition was restored after the end of the treatment. Regarding the cold sensation temperatures, both products sensitized the teeth (p<0.05) and no differences were detected between the products in each period (p>0.05). In addition, when they were compared using CoVAS, Power Bleaching caused the highest levels of sensitivity in all study periods, with the exception of the 14th day of treatment. Conclusion We concluded that the bleaching treatment sensitized the teeth and the product with potassium oxalate was not able to modulate tooth sensitivity.